Healing Center With The Orgonite Method in Mojokerto District - Karya Arsitra Rismansyah; Wiwik Widyo Widjajanti; Nareswarananindya Nareswarananindya (Jurnal IPTEK, 2023)
Jolotundo is a village in the Mojokerto Regency area that is located on the slopes of Mount Penanggungan, close to the forest and Majapahit kingdom relics. In Indonesia, public awareness of the importance of health is declining, causing bad behavior and unhealthy environmental conditions in the community. As technology advances, health technology such as orgonite becomes an effective method of treatment or restoration for both physical and psychological health. Unfortunately, no facilities provide a place to support this method. Therefore, it is necessary to have a facility that provides a place of recovery within the orgonite method based on healing and negative energy elimination for physical, mental, environmental, and spiritual well-being. This research employed field studies and literature studies as well as several methods such as observation, documentary, and interview to obtain data, both primary data as a direct data source and secondary data as other supporting data sources. The design applies the theme of therapeutic architecture, the macro concept of tropical architecture, and the micro concept of adaptive land use. The design environment involves green open spaces and maximizes landscape arrangements.